THE EVALUATION OF INVESTMENT INSTRUMENTS ON THE RUSSIAN MARKET OF GOLD - Vitaly T. Borisovich (Plekhanov Russian University of Economics, 2017)
A detailed information about gold investment vehicles has been presented in this article, investment attractiveness has been pointed out, the advantages and disadvantages of every suggested vehicle have been determined, as well as a comparative cost-benefit analysis on every investment type has been carried out according to the results of research. Common regularities and tendencies have been drawn out. It would give an investor the opportunity to make a more considered choice of investment. The author has generated formulae for efficiency calculations on every point. A constant increase of gold investment role has been detected at present and for future perspective. A new point in the problem statement is a methodological approach to the analysis of investment, affordable for private individuals in the Russian Federation.